Modeling of solid oxide fuel cell - gas turbine hybrid power plant - Tian, Yun. (2008)
The aim of this project is to develop a complete and flexible model for an integrated fuel cell/gas turbine system, and describe the operation characteristics of the hybrid system; the results then enable investigations and studies to be made on proposed configurations and designs. A general mathematical software MATLAB/SIMULINK is used as the software tool to simulate the plant performance. This model includes full load and part operation of the integrated plant. Parametric studies and part load characteristics study have been conducted.